2018
DOI: 10.1007/s12602-018-9473-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vancomycin on the Viability and Osteogenic Potential of Bone-Derived Mesenchymal Stem Cells

Abstract: Periprosthetic joint infections (PJI), caused by methicillin-resistant Staphylococcus aureus (MRSA), is the major cause of total hip arthroplasty (THA) failures. Traditionally, MRSA is treated with vancomycin, administrated intravenously or applied directly onto infected tissue. The effect of direct (as opposed to systemic) vancomycin treatment on bone formation and remodelling is largely unknown. The minimal inhibitory concentration (MIC) of vancomycin was determined by adding 200 µl of different concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Our results demonstrated that both 0.5% and 1.0% TGase can effectively cross link the gelatin/alginate/antibiotics hydrogel and achieved over 90% crosslink with better slow release of the drug up to 120 h. Even after a high dose of MRSA inoculation of this study, the vancomycin treatment group still preserved relatively high bone volume, reduced the inflammation, significant bone regeneration, more intact bony structure and less biofilm formation. This is in line with previous report that vancomycin has minimal impact on both bone marrow-derived and proximal femur-derived mesenchymal stem cells in rats [ 39 ], while serving as an effective control of the S. aureus population [ 40 , 41 ]. This also led to an improved environment for which osteogenesis can occur.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that both 0.5% and 1.0% TGase can effectively cross link the gelatin/alginate/antibiotics hydrogel and achieved over 90% crosslink with better slow release of the drug up to 120 h. Even after a high dose of MRSA inoculation of this study, the vancomycin treatment group still preserved relatively high bone volume, reduced the inflammation, significant bone regeneration, more intact bony structure and less biofilm formation. This is in line with previous report that vancomycin has minimal impact on both bone marrow-derived and proximal femur-derived mesenchymal stem cells in rats [ 39 ], while serving as an effective control of the S. aureus population [ 40 , 41 ]. This also led to an improved environment for which osteogenesis can occur.…”
Section: Discussionsupporting
confidence: 92%
“…In the existing literature, the exact effects of Vancomycin on bone formation are highly contested. While Booysen et al suggest in their 2018 study that Vancomycin has no effect whatsoever on mesenchymal stem cell viability and osteogenesis, even at high doses [44], an in vitro study by Eder et al shows that Vancomycin might interfere with bone regeneration [45]. This may be due to the decline in pH after the administration of Vancomycin at an infection site.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on the effects of vancomycin on osteogenic differentiation. The general view is that vancomycin does not adversely affect the osteogenic differentiation of human osteoblasts and human bone marrow-derived MSCs at effective antimicrobial concentrations and higher concentrations[14,24,25]. However, it has also been reported that vancomycin inhibits the osteogenic differentiation of bone marrow-derived MSCs at a concentration of 200 μg/mL[16].…”
Section: Effects Of Various Antimicrobial Agents On Osteogenic Differmentioning
confidence: 99%